Dinamika Sekolah Islam Terpadu Dikota Bengkulu - Ilham Ma'ruf; Qobi Khoiri; Moh. Iqbal (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
Dynamics of Integrated Islamic Schools in Bengkulu City The problems studied in this Writing are: (1). How the emergence and development of the Integrated Islamic School in Bengkulu City began. (2). How is the contribution of integrated Islamic schools in driving Islamic education in Bengkulu City. This paper uses This research is a type of library research. or often also called literature study, is a series of activities related to the method of collecting library data, reading and recording and processing research materials. library research.  is  a qualitative  research This writing uses a sociological approach, as well as using the theory of Fungsonalis wiliam F. Ogburn.  The research results are as follows: (1). Integrated Islamic School was first established in 1999 by the Al-Fida foundation, namely SD IT IQRA'1 Along with the changes and developments of the times, Bengkulu Muslims and also because of the needs of the Muslim Middle Community who want a Superior Islamic School, began to emerge Integrated Islamic Schools from different foundations that not only established the Elementary School level but also attended junior high schools, High school, even vocational school (2). These schools have contributed to mobilizing and fostering public interest in getting their children into Islamic educational institutions that were initially less trusted to be able to compete in public schools because for the community educational institutions only teach religious lessons.